Direitos autorais e educação : a exibição de obras cinematográficas no âmbito das Instituições Públicas de Ensino Superior do Estado de Roraima - Resplandes, Lúcia de Fátima de Souza (2022)
With the constant evolution and dissemination of technologies around the world, as well as the acquisition of electronic equipment by educational establishments, educators realized that they could improve and enrich their educational practices using media in the classroom. Thus, the use of cinematographic works has become an important auxiliary resource in the development of the teaching-learning process. The present study addresses the issue of copyright in education, debating the exhibition of protected works, in particular, cinematographic works in the educational scope. The research has as general objective to evaluate the violation of Law nº. 9.610/98 - Copyright Law (LDA) in the practice of exhibitions of cinematographic works in the classroom, in Public Institutions of Higher Education in the State of Roraima. The methodology included qualitative and quantitative approaches, with bibliographic and documentary research procedures and the application of an electronic research questionnaire. The target audience consisted of professors of undergraduate degree courses, in the face-to-face modality, from the Federal Institute of Education, Science and Technology of Roraima (IFRR), Federal University of Roraima (UFRR) and State University of Roraima (UERR). ), of the campuses located in the municipality of Boa Vista - RR. It concludes by presenting the teachers' perception in relation to copyright norms in the educational scope and their impressions about the practice of showing cinematographic works in the classroom, at Public Institutions of Higher Education in the State of Roraima. As a general rule, it was pointed out that the use of cinematographic works in educational institutions depends on the prior and express authorization of the holder or holder of the copyright of the work. Thus, it was observed the need to change the LDA, in order to create opportunities for the use of cinematographic works for the exclusive service of educational demands, aiming at the dissemination of information, access to knowledge and culture. Along with the present study, a guidebook is presented, aimed at teachers and other interested parties regarding the use of cinematographic works in the classroom of educational institutions, in the light of the LDA and related legislation.